PENERAPAN DAN EDUKASI TEKNOLOGI ARDUINO UNTUK POMPA AIR OTOMATIS PADA GREENHOUSE VEGETABLE FARM (VEFAR) - Purwanto, Ibnu Hadi; Prayoga, Galih Dwi (Jurnal Abdi Insani, 2024)
Currently agricultural production is not only focused on rice fields or gardens with a certain area. The availability of rice fields for farming according to the National Land Agency of Sleman Regency from 2016-2018 has decreased. Alternative farming in the era of millennial farmers is developing with the hydroponic method. Vegetable Farm or commonly called VEFAR has implemented a farming model using hydroponic techniques since 2019. Starting from land measuring 1000 M2 VEFAR has expanded its business to 2000 M2. The increasing number of hydroponic racks built by VEFAR has obstacles in the irrigation system. The irrigation system is still manual making irrigation for the racks late which has an impact on the adequacy of water for hydroponic plants. Agricultural technology has opened up many opportunities to increase efficiency and productivity one of which is through the use of Arduino-based automation systems. This Community Service aims to implement and teach the use of Arduino technology in an automatic water pump system for hydroponic plants. This system is designed to address the problem of inefficient and often inconsistent manual watering especially By connecting soil moisture and water level sensors to an Arduino microcontroller the system can automatically identify the amount of water needed by plants and activate the water pump at the right time based on the data collected by the sensors. The solution offered to partners is to utilize Arduino-based technology to create a water discharge controller and automatic irrigation pump in the VEFAR greenhouse. The results of the application of this technology show a significant increase in the productivity of hydroponic plants especially in terms of more consistent and efficient growth. In addition this Community Service shows that the use of an Arduino-based automatic water pump system is more efficient and environmentally friendly than conventional methods. It is hoped that education about the application of this technology will increase the understanding of VEFAR partners about the importance of technological innovation in the agricultural sector